Process Modeling of Bus Services in a Bus Station - A.M Shiddiq Yunus (Jurnal Teknologi Elekterika, 2018)
Modeling is one important parts in designing a product or a service system. It aims to reduce the cost and minimize the improper of early production/service stage that could be ended by high loss of economic value. Process modeling of bus service is required to obtain proper information regarding number of buses required based on the prediction number of passengers and time consumes. This paper is aimed to investigate the very early stage of bus service modeling using Visual Basic Excel Program. The result shows that the model system that using five inclusive sheets programming for covering the main item in the bus service system is sufficient to represent the real condition in the practical condition.